2021
DOI: 10.6007/ijarbss/v11-i19/11740
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Path Toward Family Economic Well-Being of Coconut Growers

Abstract: Many countries are establishing national programs to increase their citizens' family economic well-being. However, the concept of family economic well-being is still in its infancy, with only a few models established for developing countries. Thus, to create and implement effective policies, it is necessary to comprehend the concept family economic well-being from a multidisciplinary and multi-dimensional perspective, especially for a developing country like Sri Lanka. In the current study, path analysis was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 34 publications
3
8
0
Order By: Relevance
“…Individuals with positive financial behaviors manage their finances better to achieve higher economic well-being (Brilianti & Lutfi, 2020). Later, similar results were found by Wijekoon et al (2021a;2021b). According to Yoshino et al (2020), financial behavior plays an important role in FinTech adoption.…”
Section: Financial Behavioursupporting
confidence: 60%
See 4 more Smart Citations
“…Individuals with positive financial behaviors manage their finances better to achieve higher economic well-being (Brilianti & Lutfi, 2020). Later, similar results were found by Wijekoon et al (2021a;2021b). According to Yoshino et al (2020), financial behavior plays an important role in FinTech adoption.…”
Section: Financial Behavioursupporting
confidence: 60%
“…Lee et al (2020) found a correlation between financial knowledge and well-being. Moreover, a positive relationship between financial knowledge and economic well-being was revealed by Wijekoon et al (2021a;2021b). Further, even with different respondents and contexts financial knowledge was proved to have a positive relationship with both financial as well as economic well-being, because the concept emphasizes the importance of individuals' ability to access to financial information and financial resources in order to achieve higher economic well-being (Muller & Theuvsen, 2015).…”
Section: Financial Knowledgementioning
confidence: 94%
See 3 more Smart Citations